TWO APPROACHES IN THE INTERNATIONAL LEGAL REGULATION OF WAR - Kremena Rayanova; Teodora Yovcheva (Science & Research)

(untitled)
The topic of the research is renunciation of war as a means of international dispute settlement. As a permanent fulcrum of political philosophy and international law, war regulation applies two dynamically related focal approaches. They are either individually established or combined in various aspects. The first approach accepts war as a means of resolving disputes between sovereign states and creates rules for its humanization. The objective of the second approach is to determine international legal methods for war prevention. It is concluded that the current international law is neither based on, nor even aimed at a non-conflict foundation in international relations, but seeks its support in avoiding the wording "war".